Implications of SNP-triggered miRNA dysregulation in Schizophrenia development - Mohamed, Fadumo Abdullahi; Freude, Kristine (Frontiers in Genetics, 2024)
This review examines the substantial involvement of Single Nucleotide Polymorphisms (SNPs) and microRNAs (miRNAs) in the etiology and susceptibility to Schizophrenia, with particular emphasis on the dopaminergic, glutamatergic, and GABAergic systems. It elucidates the potential of SNPs to disrupt miRNA-mRNA interactions, leading to alterations in the regulatory mechanisms of Schizophrenia risk genes and subsequently influencing the susceptibility to Schizophrenia. Specific attention is given to the impact of SNPs in DICER, DROSHA, and DGCR8, as well as the potential for changes in DRD2 gene expression driven by miR-9 and miR-326, heightening the likelihood of Schizophrenia development. Furthermore, the review explores genetic alterations in the glutamatergic system, focusing on modifications linked to GRIN2A and its associated miRNAs, which have been reported to have a notable impact on the occurrence of Schizophrenia. Knowledge of the involvement of SNPs within miRNAs in influencing the expression of essential genes within the GABA system are emerging and described in this review, including their potential consequences for Schizophrenia.